Un itinerario travagliato: dal Codex Iuris Canonici del 1983 al nuovo Libro VI - Boni, Geraldina (Il diritto ecclesiastico, 2022)
A troubled path : from the 1983 Codex Iuris Canonici to the new Book vi · The essay dwells on a depiction of the evolution of Penal Canon Law after the Second Vatican Council up to the 1983 codification. The discourse then focuses on an illustration of the most relevant innovations that were introduced by the new Book vi of the Code of Canon Law De sanctionibus in Ecclesia, which entered into force on 8 December 2021. The spotlight is mainly centered on pointing out critical issues and problematic profiles which would deserve a careful consideration by the ecclesial legislator.